2006
DOI: 10.1002/jez.a.324
|View full text |Cite
|
Sign up to set email alerts
|

Xenobiotic detoxification in the nematode Caenorhabditis elegans

Abstract: The nematode Caenorhabditis elegans is an important model organism for the study of such diverse aspects of animal physiology and behavior as embryonic development, chemoreception, and the genetic control of lifespan. Yet, even though the entire genome sequence of this organism was deposited into public databases several years ago, little is known about xenobiotic metabolism in C. elegans. In part, the paucity of detoxification information may be due to the plush life enjoyed by nematodes raised in the laborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
151
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(154 citation statements)
references
References 69 publications
2
151
0
1
Order By: Relevance
“…We checked the enzymes in these pathways and found that the enzymes that participate in these metabolism pathways were mainly cytochromes P450 (CYPs), glutathione S-transferases (GSTs), short-chain dehydrogenases/reductases (SDRs), UDP-glucuronosyl transferases family members (UGTs) and some others (Table 4, Supplemental Tables S4 and S5). The result is similar to that found in C. elegans (Lindblom and Dodd, 2006).…”
Section: Putative Genes Related To Detoxification In the Two Nematodesupporting
confidence: 92%
See 1 more Smart Citation
“…We checked the enzymes in these pathways and found that the enzymes that participate in these metabolism pathways were mainly cytochromes P450 (CYPs), glutathione S-transferases (GSTs), short-chain dehydrogenases/reductases (SDRs), UDP-glucuronosyl transferases family members (UGTs) and some others (Table 4, Supplemental Tables S4 and S5). The result is similar to that found in C. elegans (Lindblom and Dodd, 2006).…”
Section: Putative Genes Related To Detoxification In the Two Nematodesupporting
confidence: 92%
“…They are important enzymes in xenobiotic metabolism of nematodes (Lindblom and Dodd, 2006). There were 48 and 62 transcripts of CYP450 that were found in B. xylophilus and B. mucronatus, respectively.…”
Section: Putative Genes Related To Detoxification In the Two Nematodementioning
confidence: 99%
“…To identify genes mediating the effects of indoles on healthspan, we assessed the effects of indoles on loss-of-function alleles in genes known to mediate conditioning, regulate lifespan, or modulate stress responses in C. elegans (11,13,21). These included the FOXO homolog DAF-16, the insulin receptor homolog DAF-2, the sirtuin homolog SIR2.1, the Nrf-2 homolog SKN-1, the dopamine receptor DOP-3, the tyrosine hydroxylase CAT-2, and AHR-1 (22), which encodes an ortholog of the mammalian AHR, a xenobiotic receptor that can bind to a variety of small molecules including indole (23). Similar to N2, shift in the survival curves was still evident with K12 compared with K12ΔtnaA in daf-16(m26), daf-2(e1370), sir2.1(ok434), skn-1(zu169), dop-3 (vs.106), and cat-2(e1112) animals (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…More striking still was the reduction in glutathione S-transferases (GSTs) and cytochromes P450 (CYPs), enzymes involved in xenobiotic metabolism and protection against peroxidative damage. Whereas C. elegans has 44 GSTs, including representatives from the Omega, Sigma and Zeta classes 23 Table 18).…”
Section: Protection Against Environmental Stressesmentioning
confidence: 99%